About Sibawayh, A Representative of The Basra School - Nazimjonovna, Rasulova (Indonesian Journal Publisher, 2025)
This study explores the contributions of Sibawayh, a prominent representative of the Basra school, to the development of Arabic grammar. The research aims to analyze his scholarly journey, his primary work al-Kitab, and his influence on Arabic linguistics. The study employs a historical and analytical methodology, examining primary sources and historical accounts to understand Sibawayh's linguistic theories and their impact on subsequent scholars. The findings highlight Sibawayh’s pivotal role in systematizing Arabic grammar, the theoretical foundations of al-Kitab, and his influence on linguistic debates. Despite his non-Arab origin, his dedication to the Arabic language shaped the field of Arabic grammar, solidifying his status as one of the most influential grammarians in history.